Empire and Nation: Political Ideas in Rabindranath Tagore's Travel Writings - Quayum, Mohammad Abdul (Orient BlackSwan (Orient Longman), 2011)
An investigative discussion of Rabindranath Tagore's political philosophy in his travel writings, especially with regard to his vision of the twin ideologies of Empire and Nation.